If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (42x + -7)(20 + -5x + -3) = 0 Reorder the terms: (-7 + 42x)(20 + -5x + -3) = 0 Reorder the terms: (-7 + 42x)(20 + -3 + -5x) = 0 Combine like terms: 20 + -3 = 17 (-7 + 42x)(17 + -5x) = 0 Multiply (-7 + 42x) * (17 + -5x) (-7(17 + -5x) + 42x * (17 + -5x)) = 0 ((17 * -7 + -5x * -7) + 42x * (17 + -5x)) = 0 ((-119 + 35x) + 42x * (17 + -5x)) = 0 (-119 + 35x + (17 * 42x + -5x * 42x)) = 0 (-119 + 35x + (714x + -210x2)) = 0 Combine like terms: 35x + 714x = 749x (-119 + 749x + -210x2) = 0 Solving -119 + 749x + -210x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '7'. 7(-17 + 107x + -30x2) = 0 Factor a trinomial. 7((-17 + 5x)(1 + -6x)) = 0 Ignore the factor 7.Subproblem 1
Set the factor '(-17 + 5x)' equal to zero and attempt to solve: Simplifying -17 + 5x = 0 Solving -17 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 5x = 0 + 17 Combine like terms: -17 + 17 = 0 0 + 5x = 0 + 17 5x = 0 + 17 Combine like terms: 0 + 17 = 17 5x = 17 Divide each side by '5'. x = 3.4 Simplifying x = 3.4Subproblem 2
Set the factor '(1 + -6x)' equal to zero and attempt to solve: Simplifying 1 + -6x = 0 Solving 1 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6x = 0 + -1 -6x = 0 + -1 Combine like terms: 0 + -1 = -1 -6x = -1 Divide each side by '-6'. x = 0.1666666667 Simplifying x = 0.1666666667Solution
x = {3.4, 0.1666666667}
| 3x+75=60 | | n^2-19+8=-10 | | -8.5-8+7=-26.5 | | F(x)=57(0.77) | | 6x^2-43x=75 | | -8p+7=7(1+8p) | | v+v+v+50=180 | | 18+-27= | | (6x)(1/6x3) | | F(x)=65(.64) | | 7-36/5=x | | 3(a-4b)-2(a+4b)= | | -5(-4+2x)=-10 | | 6-2u=-4 | | 3x+9y=32 | | 9x-9=-63 | | -8x+7x-9x-x= | | 20(v+3)-4v=4(4v+1)-10 | | 6x-1=-5x+10 | | -5(-4+2x)=10 | | C=mv-mu | | 20-4x=8-4(x-3) | | 11x-(5x-5)=47 | | 0.5x-1.3=-8.8 | | 3(4x-2)=10x+10 | | 4(5-x)+3=20 | | -5(1x+9)=-20 | | 2(p-4)=12 | | 6x+30=3x-3 | | 5(4a+2b)-3(2a+b)= | | 2x=180-80 | | -3.8T+4=4.4T-3 |